Minimal water exchange by the air–water valve versus left colon water exchange in unsedated colonoscopy: a randomized controlled trial - Liu, Cenqin; Zheng, Shuhao; Gao, Hui; Yuan, Xin; Zhang, Zhixin; Xie, Jiarong; Yu, Chaohui; Xu, Lei (Endoscopy, 2022)
Background Water exchange colonoscopy is the least painful method for unsedated colonoscopies. Simplified left colon water exchange (LWE) reduces the cecal intubation time but it is difficult to avoid the use of an additional pump. Minimal water exchange (MWE) is an improved novel method that eliminates the need for pumps, but it is not clear whether MWE has the same efficiency as LWE.Methods This was a prospective, randomized, controlled, noninferiority trial conducted in a tertiary hospital. Enrolled patients were randomized 1:1 to the LWE group or MWE group. The primary outcome was recalled insertion pain measured by a 4-point verbal rating scale. Secondary outcomes included adenoma detection rate (ADR), cecal intubation time, volume of water used, and patient willingness to repeat unsedated colonoscopy.Results 226 patients were included (LWE n = 113, MWE n = 113). The MWE method showed noninferior moderate/severe pain rates compared with the LWE method (10.6 % vs. 9.7 %), with a difference of 0.9 percentage points (99 % confidence interval [CI] –9.5 to 11.3; threshold, 15 %). ADR, cecal intubation time, and willingness to repeat unsedated colonoscopy were not significantly different between the two groups, but the mean volume of water used was significantly less with MWE than with LWE (163.7 mL vs. 407.2 mL; 99 %CI –298.28 to –188.69). Conclusion Compared with LWE, MWE demonstrated a noninferior outcome for insertion pain, and comparable cecal intubation time and ADR, but reduced the volume of water used and eliminated the need for a water pump.